3D printing recycled mortar mix proportion design method based on recycled fine aggregate water absorption rate
The hardened cementite content of regenerated fine aggregates is determined by dissolving salicylic acid and methanol, and the water absorption rate is predicted using linear relationships, which solves the problem of difficulty in accurately determining the water absorption rate of regenerated fine aggregates in the prior art, and realizes the coordination of 3D printing materials Improves accuracy and performance than design.
Patent Information
- Application Number
- CN202411717318.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to accurately determine the water absorption rate of regenerated fine aggregates, especially regenerated fine aggregates with smaller particle sizes, which affects the mix ratio design and performance of 3D printing materials.
The content of hardened cementite in waste concrete regenerated fine aggregates is determined by the method of salicylic acid and methanol dissolution, and the water absorption rate of regenerated fine aggregates is accurately predicted by the linear relationship equation of water absorption rate and hardened cementite content, and is used for 3D printing. Recycled mortar mix ratio design.
A more accurate determination of the water absorption rate of regenerated fine aggregates is achieved, and important parameters are provided for the mix ratio design of 3D printing materials, reducing the use of water reducers, and improving the fluidity and performance of the material.
Smart Images

Figure CN119418797A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of civil engineering materials, and in particular relates to a 3D printing recycled mortar mix design method based on a new method for testing the water absorption rate of recycled fine aggregate. Background Art
[0002] At present, the overall resource utilization rate of construction solid waste in my country is less than 30%. In addition, due to the increasing demand for various infrastructure construction, the resources of high-quality natural fine aggregate stone aggregate are becoming increasingly tight or even scarce, and its price has increased by nearly 100% in the past two years. Therefore, promoting the crushing of construction solid waste (waste concrete) into recycled aggregate, partially replacing natural aggregate and preparing recycled concrete for actual engineering is of great significance to the sustainable development of the construction industry and the promotion of the construction of "zero-waste cities".
[0003] However, it is difficult to effectively utilize the recycled fine aggregate in the process of resource utilization. This is mainly because compared with natural fine aggregate, the surface of recycled fine aggregate is attached with old cement stone. The content of hardened cement stone is an important factor affecting the water absorption rate of recycled fine aggregate based on waste concrete. However, the current methods for determining the content of hardened cement stone in recycled aggregate are mainly heat treatment method, hydrochloric acid treatment method, image analysis method, etc., which are not suitable for the determination of hardened cement stone in recycled fine aggregate, especially the recycled fine aggregate prepared from the calcium-containing aggregate of the previous generation of waste concrete. In addition, the water absorption rate of recycled fine aggregate with a smaller particle size (0 / 0.63mm) is difficult to accurately determine.
[0004] Using 3D printing technology for digital construction is a technical approach to solve many problems of traditional construction modes, and it has been increasingly studied. If recycled fine aggregate can be converted into materials that can be used for 3D printing, the above problems will be well solved. However, for 3D printing, the material needs to have both good pumping and extrusion performance, as well as special rheological properties to meet specific extrudability and buildability requirements. For the use of recycled fine aggregate to 3D print building materials, the hardened materials also have corresponding mechanical properties and volume stability and other requirements. In order to meet these requirements, it is also necessary to be able to very accurately measure the water absorption of recycled fine aggregate and design the corresponding 3D printing material mix ratio based on the measured water absorption. There is currently a lack of such methods. Summary of the invention
[0005] The present invention is carried out to solve the above problems. One of the purposes is to provide a test method that can more accurately determine the water absorption rate of recycled fine aggregate, and the second purpose is to further provide a 3D printing material mix design method based on the accurate water absorption rate of recycled fine aggregate. The method adopted by the present invention is to first determine the content of hardened cement stone in the recycled fine aggregate of waste concrete by salicylic acid and methanol dissolution determination method, and then accurately predict the water absorption rate of recycled fine aggregate with finer particle size of waste concrete and the water absorption rate of recycled fine aggregate (0 / 5mm), which are applied to the design of 3D printing recycled mortar mix, so as to achieve fluidity that meets the requirements of 3D printing and reduce the use of water reducer.
[0006] Specifically, the present invention adopts the following technical solutions:
[0007] The present invention provides a 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate. The method has the following characteristics: the method comprises the following steps: step S1, using the national standard method to respectively determine the water absorption rates of recycled fine aggregates of various particle sizes; step S2, using salicylic acid and methanol dissolution methods to respectively determine the hardened cement stone content of the recycled fine aggregates of various particle sizes; step S3, according to the water absorption rate measured in step S1 and the hardened cement stone content measured in step S2, obtain the linear relationship between the water absorption rate and the hardened cement stone content of the recycled fine aggregates of the various particle sizes; step S4, according to the relationship obtained in step S3, the particle size distribution curves of each group of recycled fine aggregates of different particle sizes and the corresponding water absorption rates, calculate the water absorption rate of the recycled fine aggregate of a specific particle size; step S5, according to the water absorption rate of the recycled fine aggregate of the specific particle size obtained in step S4, design the 3D printing recycled mortar mix design.
[0008] The 3D printing recycled mortar mix ratio design method based on the water absorption rate of recycled fine aggregate provided by the present invention may also have such a technical feature, wherein, in step S5, the 3D printing recycled mortar mix ratio includes the ratio of cement dosage, fine aggregate dosage, recycled fine aggregate dosage, water dosage, additional water dosage, and water reducing agent dosage, and the additional water dosage is W*×Z×A%, wherein W* is the water absorption rate of the recycled fine aggregate of the specific particle size obtained according to step S4, Z is the fine aggregate dosage, and A% is the recycled fine aggregate replacement rate.
[0009] The 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate provided by the present invention may also have such a technical feature, wherein step S2 includes the following sub-steps: step S2-1, weighing a sample of the recycled fine aggregate according to a predetermined formula, and drying, grinding and sieving the sample to obtain sample one, and weighing the sample one; step S2-2, adding the sample one and salicylic acid into a methanol solution and stirring to dissolve the sample one to obtain a mixture one; step S2-3, filtering the mixture one and washing it with a methanol solution for multiple times to obtain a mixture two; step S2-4, drying the mixture two to obtain a mixture three; step S2-5, weighing the mixture three, and calculating the hardened cement stone content of the sample based on the weight of the sample one and the weight of the mixture three.
[0010] The 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate provided by the present invention may also have such a technical feature, wherein, in step S1, the recycled fine aggregates of three particle sizes are tested respectively, and the particle sizes are 0.63 / 1.25mm, 1.25 / 2.5mm, and 2.5 / 5mm, respectively, and their water absorption rates W1, W2, and W3 are measured respectively; in step S2, the samples of the recycled fine aggregates of four particle sizes are tested respectively, and their hardened cement stone contents C0, C1, C2, and C3 are measured respectively; in step S3, the linear regression equation of the water absorption rate of the recycled fine aggregate and the hardened cement stone content is fitted according to the water absorption rates W1, W2, and W3 of the three particle sizes and the corresponding hardened cement stone contents C1, C2, and C3:
[0011] y=ax+b
[0012] In the formula, a and b are coefficients, x represents the content of hardened cement paste, and y represents the water absorption rate.
[0013] The 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate provided by the present invention may also have such a technical feature, wherein, in step S4, the calculation formula of the water absorption rate is:
[0014] W^*=W1×β1+W2×β2+W3×β3+W0×β0
[0015] Wherein, β0, β1, β2, and β3 are the mass fractions of 0 / 0.63 mm, 0.63 / 1.25 mm, 1.25 / 2.5 mm, and 2.5 / 5 mm particle sizes to 0 / 5 mm particle size, respectively, which are obtained from the particle size distribution curve.
[0016] The 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate provided by the present invention may also have such technical features, wherein, in step S2-1, 0.5g of the sample is weighed, the sample is dried at 105°C to constant weight, and ground to pass through a 0.2mm sieve to obtain the sample one, in step S2-2, the sample one and 14g of salicylic acid are dissolved in 80ml of methanol solution, and stirred to dissolve the sample one to obtain the mixture one, in step S2-3, the mixture one is placed on a glass filter to filter to obtain a solid part, and washed 4 times with a methanol solution to obtain the mixture two, and in step S2-4, the mixture two is dried at a temperature of 70°C to obtain the mixture three.
[0017] The 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate provided by the present invention can also have such technical characteristics, wherein, in step S2-2, the stirring speed is 20r / min, the stirring time is 1h, in step S2-3, the pore size of the glass filter is 10-16μm, and the mixture 1 is placed at a height of 2-3mm from the top of the glass filter for filtering, and in step S2-4, the mixture 2 is dried in an oven for 30min.
[0018] The 3D printing recycled mortar mix design method based on recycled fine aggregate water absorption provided by the present invention may also have such a technical feature, wherein in step S2-5, the calculation formula of the hardened cement stone content is:
[0019]
[0020] Where M1 is the weight of sample one, and M2 is the weight of mixture three.
[0021] Functions and Effects of the Invention
[0022] According to the 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate provided by the present invention, the content of hardened cement stone in the recycled fine aggregate is first determined based on the method of dissolving the recycled fine aggregate of waste concrete with salicylic acid and methanol, and the water absorption rate of finer particles is obtained through the linear regression equation of the content of hardened cement stone with different particle sizes and the water absorption rate. This method is more accurate for the water absorption rate of recycled fine aggregate with fine particle size than the national standard GB / T 14684-2022.
[0023] Furthermore, the water absorption rate of the relatively fine-sized recycled fine aggregate obtained by the above method provides an important parameter for the mix design of 3D printed recycled fine aggregate mortar / concrete based on recycled fine aggregate, controls the dosage of water reducer, and ensures its excellent fluidity, which is of great significance for the preparation of 3D printed recycled fine aggregate mortar / concrete, and also helps to improve the resource utilization rate of recycled fine aggregate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a flow chart of a 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate in an embodiment of the present invention;
[0025] Figure 2 4 is a flow chart of step S2 in an embodiment of the present invention. DETAILED DESCRIPTION
[0026] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following is a specific description of the 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate in combination with the embodiments and drawings.
[0027] <Example 1>
[0028] The present embodiment provides a method for designing a mix ratio of 3D printed recycled mortar based on the water absorption rate of recycled fine aggregate. The water absorption rates of recycled fine aggregates of various particle sizes are firstly accurately tested, and then the mix ratio of 3D printed recycled mortar is designed based on the measured water absorption rates.
[0029] In this embodiment, before starting the method, recycled fine aggregates of four particle sizes are prepared in the following manner:
[0030] After the original concrete was prepared in the laboratory, the original concrete was crushed with a jaw crusher (after curing for 28 days) to obtain recycled fine aggregate. The original concrete mix ratio was: coarse aggregate 1138.3kg / m3, fine aggregate 756.4kg / m3, cement 298.8kg / m3, and water-cement ratio 0.6. After the original concrete was cured in water for 28 days, the original concrete was crushed with a jaw crusher, and the crushed recycled fine aggregate (0-5mm) was dried in an oven at 105℃. Then the 0 / 5mm recycled fine aggregate was sieved and separated according to 4 different particle sizes (0 / 0.63, 0.63 / 1.25, 1.25 / 2.5, 2.5 / 5mm), and representative samples of each group were taken as test specimens.
[0031] Figure 1 It is a flow chart of the 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate in this embodiment.
[0032] like Figure 1 As shown, the method comprises the following steps:
[0033] Step S1, using the national standard method to measure the water absorption rate of recycled fine aggregates of various particle sizes.
[0034] In this embodiment, the national standard GB / T 14684-2022 is used to measure the water absorption rate of recycled fine aggregates with three particle sizes, and the three particle sizes are 0.63 / 1.25 mm, 1.25 / 2.5 mm, and 2.5 / 5 mm, respectively. The measured water absorption rates are recorded as W1, W2, and W3, respectively.
[0035] Step S2, using salicylic acid and methanol dissolution methods to respectively determine the hardened cement paste content of recycled fine aggregates of various particle sizes.
[0036] Among them, the hardened cement stone content of recycled fine aggregate with four particle sizes was determined by the salicylic acid and methanol dissolution method. In this embodiment, the four particle sizes were 0 / 0.63mm, 0.63 / 1.25mm, 1.25 / 2.5mm, and 2.5 / 5mm, respectively. The measured hardened cement stone contents were recorded as C0, C1, C2, and C3, respectively.
[0037] Figure 2 is a flow chart of step S2 in this embodiment.
[0038] like Figure 2 As shown, step S2 specifically includes the following sub-steps:
[0039] Step S2-1, weighing a sample according to a predetermined formula, drying, grinding and sieving the sample to obtain a sample 1, and weighing the sample;
[0040] Step S2-2, adding sample 1 and salicylic acid into a methanol solution and stirring to dissolve sample 1 to obtain mixture 1;
[0041] Step S2-3, filtering the mixture 1, and washing it with a methanol solution for multiple times to obtain a mixture 2;
[0042] Step S2-4, drying the mixture 2 to obtain a mixture 3;
[0043] Step S2-5, weighing the mixture three, and calculating the hardened cement content of the sample based on the weight of the sample one and the weight of the mixture three, the calculation formula is:
[0044]
[0045] Where M1 is the weight of sample one, and M2 is the weight of mixture three.
[0046] In this embodiment, in step S2-1, 0.5 g of the sample is weighed, dried at 105°C to constant weight, ground to pass through a 0.2 mm sieve, and sample 1 is obtained, and sample 1 is weighed. The samples are four recycled fine aggregates of different particle sizes prepared according to the above method of this embodiment, and their particle sizes are 0 / 0.63 mm, 0.63 / 1.25 mm, 1.25 / 2.5 mm, and 2.5 / 5 mm, respectively.
[0047] In step S2-2, sample 1 and 14 g of salicylic acid were dissolved in 80 ml of methanol solution according to the formula, and stirred at a stirring speed of 20 r / min for 1 h to dissolve sample 1, thereby obtaining mixture 1.
[0048] In step S2-3, mixture 1 is placed on a glass filter with a pore size of 10-16 μm (2-3 mm above the top of the filter) for filtration to obtain a solid portion, and washed 4 times with a methanol solution to obtain mixture 2, which is a solid residue.
[0049] In step S2-4, the mixture 2 (solid residue) is dried in an oven at 70° C. for 30 min to obtain a mixture 3;
[0050] In step S2-5, the mixture three is weighed, and the hardened cement paste content of the recycled fine aggregate with particle sizes of 0 / 0.63 mm, 0.63 / 1.25 mm, 1.25 / 2.5 mm, and 2.5 / 5 mm is calculated according to the above formula. The results are shown in Table 1 below.
[0051] Table 1 Recycled fine aggregate hardened cement paste content (%) of the above samples
[0052] Particle size 0 / 0.63mm 0.63 / 1.25mm 1.25 / 2.5mm 2.5 / 5mm Example 1 26.5 25.0 23.3 19.4
[0053] In this embodiment,
[0054] Table 2 Comparison of water absorption rate of each group of recycled fine aggregate and predicted value of 0 / 0.63 mm with experimental value
[0055]
[0056] Step S3, according to the water absorption rate measured in step S1 and the hardened cement paste content measured in step S2, the linear relationship between the water absorption rate and the hardened cement paste content of the recycled fine aggregates of various particle sizes is obtained.
[0057] Among them, the water absorption rate of recycled fine aggregate with three particle sizes was measured according to the national standard, and the hardened cement paste content of the corresponding recycled fine aggregate with three particle sizes was measured by the salicylic acid and methanol dissolution method. The linear regression equation of the water absorption rate of recycled fine aggregate and the hardened cement paste content was fitted:
[0058] y=ax+b
[0059] In the formula, a and b are coefficients, x i (i is 1, 2, 3) corresponding to C1, C2, C3, y i (i is 1, 2, 3) corresponding to W1, W2, and W3 respectively.
[0060] Then, the water absorption rate of recycled fine aggregate with a particle size of 0 / 0.63 mm was obtained according to the linear regression equation:
[0061] y=ax+b
[0062] Where x corresponds to C0, and y is the water absorption rate of recycled fine aggregate with a particle size of 0 / 0.63 mm.
[0063] Step S4, calculating the water absorption rate of the recycled fine aggregate with a specific particle size according to the relationship obtained in step S3, the particle size distribution curves of each group of recycled fine aggregates with different particle sizes and the corresponding water absorption rates.
[0064] Among them, according to the particle size distribution curve and the corresponding water absorption rate, the water absorption rate W* of the recycled fine aggregate with a particle size of 0 / 5 mm is calculated, and the calculation equation is:
[0065] W * =W1×β1+W2×β2+W3×β3+W0×β0
[0066] Wherein, β0, β1, β2, and β3 are the mass fractions of particle size of 0 / 5 mm, 0.63 / 1.25, 1.25 / 2.5, and 2.5 / 5 mm, respectively, which can be obtained from the particle size distribution curve.
[0067] In this embodiment, according to the particle size distribution curves of each group of recycled fine aggregates with different particle sizes and the corresponding water absorption values, the water absorption of the recycled fine aggregate with a particle size of 0 / 5 mm is calculated to be 15.2%.
[0068] Step S5, designing a mix ratio of 3D printing recycled mortar according to the water absorption rate of the recycled fine aggregate with a specific particle size obtained in step S4.
[0069] Among them, the mix ratio of 3D printed recycled mortar includes the ratio of cement dosage, fine aggregate dosage, recycled fine aggregate dosage, water dosage, additional water dosage and water reducing agent dosage.
[0070] The calculated water absorption rate of recycled fine aggregate is W*, the amount of fine aggregate is Z, the replacement rate of recycled fine aggregate is A%, and the additional water consumption is W*×Z×A%.
[0071] In this embodiment, the calculated water absorption rate of the recycled fine aggregate with a particle size of 0 / 5 mm is 15.2%, the recycled fine aggregate replacement rate is set to 30%, and the amount of fine aggregate is set to 1. The additional water amount can be calculated according to the above formula, and the amount of water reducer can be further calculated in combination with the target water-cement ratio.
[0072] In addition, the method of this embodiment was compared and verified. After the mix ratio was obtained by the above method of this embodiment, the corresponding sample was prepared according to the mix ratio as the experimental group RA-30 / T; and the water absorption of the above sample was tested using the national standard GB / T 14684-2022 (standard for testing the water absorption of natural sand), and the water absorption was measured to be 14.3%. Then, according to the water absorption, the corresponding mix ratio was obtained through step S5, and the corresponding sample was prepared according to the mix ratio as the control group RA-30. The mix ratios of the experimental group and the control group are shown in Table 3 below:
[0073] Table 3 3D printing mortar mix design in implementation case 1
[0074]
[0075] After testing, the diffusion of the experimental group and the control group was 170mm+-5mm, the compressive strength of the experimental group RA-30 / T was 21.5-30.5MPa, and the compressive strength of the control group RA-30 was 22.7-30.4Mpa. As shown in Table 3, the water absorption rate of the recycled fine aggregate was more accurately tested by the method of this embodiment, and the mix ratio was designed based on the water absorption rate, which effectively reduced the amount of water reducer.
[0076] <Example 2>
[0077] The present embodiment provides a 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate. In the present embodiment, the same symbols are given to the same components as those in the first embodiment and the corresponding descriptions are omitted.
[0078] Compared with Example 1, the difference is that in the method of this embodiment, before starting the method, recycled fine aggregates of four particle sizes are prepared in the following manner:
[0079] After the original concrete was prepared in the laboratory, the recycled fine aggregate was obtained by crushing the original concrete (after curing for 28 days) with a jaw crusher. The original concrete mix ratio was: coarse aggregate 1040.7 kg / m 3 , fine aggregate 691.5kg / m 3 、Cement 375.7kg / m 3, water-cement ratio of 0.6. After the original concrete was cured in water for 28 days, it was crushed by a jaw crusher, and the crushed recycled fine aggregate (0-5mm) was dried in an oven at 105℃. Then, it was sieved and separated according to 4 different particle sizes (0 / 0.63, 0.63 / 1.25, 1.25 / 2.5, 2.5 / 5mm), and representative samples of each group were taken as specimens.
[0080] Then, the water absorption is measured according to steps S1 to S5 of the first embodiment and the mix ratio is designed based on the water absorption.
[0081] In this embodiment, after step S2, the hardened cement paste content of each sample is measured as shown in the following Table 4:
[0082] Table 4 Recycled fine aggregate hardened cement paste content (%) of the above samples
[0083] Particle size 0 / 0.63mm 0.63 / 1.25mm 1.25 / 2.5mm 2.5 / 5mm Example 2 32.7 29.5 27.1 23.2
[0084] After step S4, the water absorption rate of each sample and the experimental value are determined as shown in the following Table 5:
[0085] Table 5 Comparison of water absorption of each group of recycled fine aggregate and predicted value of 0 / 0.63 mm with experimental value
[0086]
[0087]
[0088] Similarly, the method of this embodiment is also compared and verified. After the mix ratio is obtained by the above method of this embodiment, the corresponding sample is prepared according to the mix ratio as the experimental group RA-50T. The water absorption rate of the recycled fine aggregate of the RA-50T group is 17.7%; and the national standard GB / T14684-2022 (used to test the water absorption rate of natural sand) is used to test the water absorption rate of the above sample, and the water absorption rate is measured to be 16.4%. Then, according to the water absorption rate, the corresponding mix ratio is obtained through step S5, and the corresponding sample is prepared according to the mix ratio as the control group RA-50. The mix ratios of the experimental group and the control group are shown in Table 6 below:
[0089] Table 6 3D printing mortar mix design in implementation case 2
[0090]
[0091] After testing, the compressive strength of the experimental group RA-50 / T was 19.4-26.2MPa, and the compressive strength of the control group RA-50 was 19.0-25.9MPa. As shown in Table 3, the water absorption rate of the recycled fine aggregate was more accurately tested by the method of this embodiment, and the mix ratio was designed based on the water absorption rate, which effectively reduced the amount of water reducing agent.
[0092] In this embodiment, other method steps are the same as those in the first embodiment, and thus will not be described again.
[0093] Functions and Effects of the Embodiments
[0094] According to the 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate provided in the embodiment, the content of hardened cement stone in the recycled fine aggregate is first determined based on the method of dissolving the recycled fine aggregate of waste concrete with salicylic acid and methanol. The water absorption rate of finer particles is obtained through the linear regression equation of the content of hardened cement stone with different particle sizes and the water absorption rate. This method is more accurate for the water absorption rate of recycled fine aggregate with fine particle size than the national standard GB / T 14684-2022.
[0095] In the embodiment, salicylic acid and methanol solution are used to dissolve waste concrete. The characteristic of salicylic acid is that it can dissolve most of the components of cement stone, but it will not dissolve natural aggregate, especially the main component of calcareous aggregate (limestone), which ensures the specificity and accuracy of the method. The experimental process of this method is concise and efficient, including the steps of drying, grinding, dissolving, filtering, re-drying and weighing of the sample, which ensures the simplicity and feasibility of the operation. In addition, the inventors have verified the high accuracy and excellent repeatability of this method through multiple comparative experiments, and can stably and reliably determine the content of hardened cement stone, and can be used to predict the water absorption rate of the finer particle size recycled fine aggregate of waste concrete, thereby guiding the mix design of 3D printed recycled mortar.
[0096] The method of the present invention has wide applicability, and can accurately determine the water absorption rate of relatively fine particle size recycled fine aggregate. The water absorption rate of relatively fine particle size recycled fine aggregate obtained by the method is more accurate than the value based on the national standard GB / T 14684-2022, and provides important parameters for the mix ratio design of 3D printed recycled fine aggregate mortar / concrete based on recycled fine aggregate. It is of great significance for the preparation of recycled fine aggregate mortar / concrete, and helps to provide the resource utilization rate of recycled fine aggregate, meet the requirements of sustainable development and environmental protection, comply with the construction of waste-free cities and the national dual-carbon strategy, and help the green and low-carbon transformation of the construction industry.
[0097] The above embodiments are only used to illustrate the specific implementation of the present invention, and the present invention is not limited to the description scope of the above embodiments. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only to illustrate the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate, characterized in that: The following steps are involved: Step S1, using the national standard method to measure the water absorption rate of recycled fine aggregates of various particle sizes; Step S2, using salicylic acid and methanol dissolution methods to respectively determine the hardened cement paste content of the recycled fine aggregates of various particle sizes; Step S3, according to the water absorption rate measured in step S1 and the hardened cement paste content measured in step S2, a linear relationship between the water absorption rate and the hardened cement paste content of the recycled fine aggregates of the various particle sizes is obtained; Step S4, calculating the water absorption rate of the recycled fine aggregate of a specific particle size according to the relationship obtained in step S3, the particle size distribution curves of each group of recycled fine aggregates of different particle sizes and the corresponding water absorption rates; Step S5, designing a 3D printing recycled mortar mix ratio according to the water absorption rate of the recycled fine aggregate of the specific particle size obtained in step S4.
2. The 3D printing recycled mortar mix design method based on recycled fine aggregate water absorption rate according to claim 1 is characterized in that: in, In step S5, the 3D printing recycled mortar mix ratio includes the ratio of cement dosage, fine aggregate dosage, recycled fine aggregate dosage, water dosage, additional water dosage, and water reducing agent dosage. The additional water dosage is W*×Z×A%, wherein W* is the water absorption rate of the recycled fine aggregate of the specific particle size obtained in step S4, Z is the amount of the fine aggregate, and A% is the replacement rate of the recycled fine aggregate.
3. According to claim 1, the 3D printing recycled mortar mix design method based on the water absorption rate of recycled fine aggregate, Features: Wherein, step S2 includes the following sub-steps: Step S2-1, weighing a sample of the recycled fine aggregate according to a predetermined formula, drying, grinding and sieving the sample to obtain a sample 1, and weighing the sample 1; Step S2-2, adding the sample 1 and salicylic acid into a methanol solution and stirring to dissolve the sample 1 to obtain a mixture 1; Step S2-3, filtering the mixture 1, and washing it with a methanol solution for multiple times to obtain a mixture 2; Step S2-4, drying the mixture 2 to obtain a mixture 3; Step S2-5, weighing the mixture three, and calculating the hardened cement stone content of the sample based on the weight of the sample one and the weight of the mixture three.
4. The 3D printing recycled mortar mix design method based on recycled fine aggregate water absorption rate according to claim 3 is characterized in that: in, In step S1, three particle sizes of the recycled fine aggregate are tested, namely 0.63 / 1.25 mm, 1.25 / 2.5 mm, and 2.5 / 5 mm, and their water absorption rates W1, W2, and W3 are measured respectively. In step S2, samples of the recycled fine aggregate of four particle sizes are tested respectively, and their hardened cement paste contents C0, C1, C2, and C3 are measured respectively. In step S3, the linear regression equation of the water absorption rate of the recycled fine aggregate and the hardened cement paste content is obtained by fitting according to the water absorption rates W1, W2, W3 of the three particle sizes and the corresponding hardened cement paste contents C1, C2, C3: y=ax+b In the formula, a and b are coefficients, x represents the content of hardened cement paste, and y represents the water absorption rate.
5. The 3D printing recycled mortar mix design method based on recycled fine aggregate water absorption rate according to claim 4 is characterized in that: in, In step S4, the calculation formula of the water absorption rate is: IN * =W1×β1+W2×β2+W3×β3+W0×β0 Wherein, β0, β1, β2, and β3 are the mass fractions of 0 / 0.63 mm, 0.63 / 1.25 mm, 1.25 / 2.5 mm, and 2.5 / 5 mm particle sizes to 0 / 5 mm particle size, respectively, which are obtained from the particle size distribution curve.
6. The 3D printing recycled mortar mix design method based on recycled fine aggregate water absorption rate according to claim 3 or 4, characterized in that: in, In step S2-1, 0.5 g of the sample is weighed, dried at 105° C. to constant weight, and ground to pass through a 0.2 mm sieve to obtain sample 1. In step S2-2, sample 1 and 14 g of salicylic acid are dissolved in 80 ml of methanol solution, and stirred to dissolve the sample 1 to obtain the mixture 1. In step S2-3, the mixture 1 is placed on a glass filter and filtered to obtain a solid portion, and then washed with a methanol solution for 4 times to obtain the mixture 2. In step S2-4, the mixture 2 is dried at a temperature of 70°C to obtain the mixture 3.
7. The 3D printing recycled mortar mix design method based on recycled fine aggregate water absorption rate according to claim 6 is characterized in that: in, In step S2-2, the stirring speed is 20 r / min and the stirring time is 1 h. In step S2-3, the pore size of the glass filter is 10-16 μm, and the mixture is placed at a height of 2-3 mm from the top of the glass filter for filtering. In step S2-4, the mixture is dried in an oven for 30 minutes.
8. The 3D printing recycled mortar mix design method based on recycled fine aggregate water absorption rate according to claim 6 is characterized in that: in, In step S2-5, the calculation formula of the hardened cement paste content is: Where M1 is the weight of sample one, and M2 is the weight of mixture three.